Contestation, Negotation and Culture in the Reconstruction of Riau's Identity - Lugina Setyawati (Antropologi Indonesia, 2011)
This paper explained the issue of inequality which appears in the process of democratization through the analysis of contestation, negotiation, and the reconstruction of Riau’s identity. Ideally, democratic principles respect equality; however, identity expresses inequality because it defines who is dominant and subordinate in a certain social group through ethnic category and gender identity. It separates the insiders and outsiders with different rights through cultural idioms. Moreover, the identity is not merely applied in the private domain, but also in the public sphere. This paper resulted from research conducted in Riau Province in a periode of decentralization process. The findings shown that In daily practice the collective sentiments manifested in the notion of “Putra Daerah” may create problems, as this notion is not only used as a social category to define collective boundaries, but also as a strategic tool to control access to political and economic power in Riau. Quoting Worsley, Cultural traits are not absolute or simply intellectual categories, but are invoked to provide identities which legitimize claims to rights. They are strategies or weapons in competitions over scarce social goods Worsley (1994). Keyword: contestation, reconstruction of identity, woman perspective, decentralization